Impression management as symbolic capital: an intercultural comparison of presentations by CEOs on social network sites - Lueg, Klarissa; Nielsen, Camilla (Communication & Language at Work, 2015)
Social Network Sites (SNS) play an increasingly important role in the European business world, especially with respect to cross-cultural impression management. Departing from the Bourdieusian concept of “capital,” this paper analyzes the differences in the use of two popular business SNS: XING in Germany and LinkedIn in Denmark. We summarize those differences and relate them to different cultural contexts and impression management practices. Our sample consists of Danish Higher Executives (HEs)/managers (e.g., CEOs) and companies that have profiles on both SNS, thus reaching out to both the German and the Danish markets. It is apparent that even business experts operating in both markets could better adapt to the standards and possibilities offered by the German SNS with respect to impression management. We introduce a set of recommendations to foster SNS-related and culture-sensitive impression management.